1990
DOI: 10.1248/cpb.38.123
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of in vitro antitumor activities of platinum complexes.

Abstract: Factor analysis was applied to the data matrix of in vitro growth inhibitory activities of 52 platinum complexes against 9 tumor cell lines, L1210, P388, Lewis lung, AH66, AH66F, HeLa S3, KB, HT-1197 and HT-1376 cell lines. Three factors were obtained by the principal factor analysis method. After the varimax rotation of these three factors, tumor cell lines were classified into four groups according to their factor loadings. The platinum complexes were characterized by the factor scores. Cisplatin was situate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Several studies have provided evidence for a physiological role of sEpoR by direct competition for Epo with mEpoR, and also for an effect of hypoxia on sEpoR levels ( 5 , 9 , 23 , 26 , 32 , 43 ). It has been shown, for example, that changes in plasma sEpoR concentration influence the effect of Epo on Hb concentration ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have provided evidence for a physiological role of sEpoR by direct competition for Epo with mEpoR, and also for an effect of hypoxia on sEpoR levels ( 5 , 9 , 23 , 26 , 32 , 43 ). It has been shown, for example, that changes in plasma sEpoR concentration influence the effect of Epo on Hb concentration ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have provided evidence for a role of sEpoR in modulating Epo signaling as sEpoR blocks Epo signaling in vitro and in vivo by direct competition for Epo with mEpoR ( 5 , 26 , 32 , 43 ). The presence of sEpoR has been reported in plasma and several tissues, including liver, spleen, kidney, muscle, brain, and bone marrow ( 14 , 32 , 43 ).…”
mentioning
confidence: 99%
“…First, other investigators have shown that sEpoR may block EpoR signaling in vitro [25], [51]. Second there is recent data to suggest that sEpoR may inhibit erythropoietin signaling in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Pattern recognition techniques, like multivariate statistics, will be used in order to investigate activity and selectivity. Similar techniques have been successfully used on other cytostatic activity data. These papers discouraged the use of one single experiment for the determination of biological activity. Principal component analysis helps in reducing data from a number of experiments to the underlying patterns of information. New properties, called principal components, are derived by linear combination of the old properties, assigning contributions to the old properties in an interative manner.…”
Section: Introductionmentioning
confidence: 99%
“…Similar techniques have been successfully used on other cytostatic activity data. [35][36][37] These papers discouraged the use of one single experiment for the determination of biological activity. Principal component analysis helps in reducing data from a number of experiments to the underlying patterns of information.…”
Section: Introductionmentioning
confidence: 99%